Rationality and Public Policy: Studi Kasus: Absennya Kebijakan Berperspektif Gender dalam Menangani Kebakaran Lahan Gambut Pada 2019 - Shera; Aldrin Pasha, Julian (Talenta Publisher, 2020)
Indonesia is a country with vast forest and peatland areas. However, this is in line with the destruction of the forest and peatlands. Peatland fires in Indonesia are quite alarming, which have a wide impact on various aspects of life, including the environment, health, social and economy, the impacts of which are specifically experienced by women. Various policies have been taken by the government. However, in reality these policies are more likely to attempt to extinguish forest and peat fires, not yet answering thoroughly about the problems and impacts behind them experienced by women. This happens because there are problems in the step of formulating the problems of these policies, also the rationality used is not yet fully gender perspective.